Effects of Group Activity Therapy: Planting and Drawing on Decreasing Depression Rates In the elderly with Non-Communicable Diseases (NCDs) - Asti Nuraeni; Ellia Putri Agustina C; Mamat Supriyono (UIMA Press, 2023)
Background: The elderly experience physical and psychosocial changes that result in non-communicable diseases. The impact of the elderly experiencing a health problem causes depression. Elderly with NCDs who experience depression need tertiary prevention. Level prevention that can be done aims to improve the quality of life. Objectives: The purpose of this study was to determine the effect of group activity therapy on reducing the level of depression in the elderly with non-communicable diseases. Methods: This research method used a quasy experimental pre & post test design in one intervention group. The sampling technique used was simple random sampling with a total of 58 respondents. The statistical test used is the Wilxocon test. Results: The results showed that there was a significant effect before and after being given group activity therapy by planting and drawing on a decrease in the level of depression in the elderly with a p-value = 0.001 (p ≤ 0.05). Conclusion: There is an influence between group activity therapy by planting and drawing on a decrease in the level of depression in the elderly. The implications of the results of this study are group activity therapy carried out on the elderly with NCDs can be carried out periodically through monthly activities in the community.